System device and method for strengthening liquid-solid mass transfer through supergravity

By designing the supergravity-strengthening liquid-solid mass transfer system device, the multi-layer filler area and loading area structure is used to solve the problems of low liquid-solid mass transfer efficiency and poor dispersion, which significantly improves the permeability and catalysis of the catalyst performance.

CN119281245AActive Publication Date: 2025-01-10BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411354031.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

In the prior art, the liquid-solid mass transfer efficiency is low and the dispersion is poor, making it difficult to effectively transfer the mass between the solid powder and the liquid, especially affecting the catalytic performance during the catalyst impregnation process.

Method used

Design a supergravity reinforcement liquid-solid mass transfer system device, including an external circulation supergravity reactor, a circulation tank, a circulation pump and a motor, fixing the wire mesh filler and solid powder through a multi-layer structure in the filler and loading area, and using rotation The liquid is cut into nano-scale droplets or liquid lines to improve the mass transfer efficiency of liquid-solid mixing.

Benefits of technology

The liquid-solid mass transfer efficiency and dispersion are significantly improved, the permeability and catalytic performance of the catalyst are improved, and the problems of low mass transfer efficiency and poor dispersion are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281245A_ABST
    Figure CN119281245A_ABST
Patent Text Reader

Abstract

The invention discloses a system device and method for strengthening liquid-solid mass transfer through supergravity. The system device comprises an outer circulation supergravity reactor, a circulation tank, a circulation pump, a motor and a valve. The external circulation supergravity reactor comprises a feed port, a discharge port, an air inlet, an air outlet, a liquid distributor and reactor internals; the reactor internal component is composed of a stand column, a filler area and a filling area; the motor is fixedly connected with the reactor internal component through a transmission shaft, and the motor rotates to drive the reactor internal component to rotate; multiple layers of filling areas and multiple layers of filling areas are arranged, the multiple layers of filling areas and the multiple layers of filling areas are concentrically arranged at intervals, and the stand columns are fixedly arranged in the filling areas or at the edges of the filling areas; the liquid distributor is arranged at the position of a central cavity of the reactor internal component; and the discharge port, the circulating tank, the circulating pump, the feed port and the reactor internal components are sequentially communicated through pipelines. The system device can fix solid powder and strengthen liquid dispersion, and is high in efficiency and good in dispersity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of enhancing liquid-solid mass transfer, and in particular relates to a system device and a method for enhancing liquid-solid mass transfer by ultra-gravity. Background Art

[0002] There are many preparation methods for industrial catalysts, but for supported catalysts, the impregnation process is one of the most important steps in catalyst preparation. The impregnation process generally involves immersing the carrier in an impregnation solution. After a period of time, the carrier is filtered, washed, dried, and other operations are performed to obtain a catalyst loaded with active components. Catalyst carriers are generally porous media, such as activated carbon, molecular sieves, MOF, COF, alumina and other materials, which can not only increase the specific surface area of ​​the catalyst, improve heat resistance and mechanical strength, but also act as co-catalysts or promoters; and the impregnation solution generally dissolves the active component in a solvent to form a uniformly dispersed active component solution. There are various types and preparation methods of impregnation solutions. For example, the RLF impregnation solution is an emulsion of a certain concentration obtained by reacting resorcinol with formaldehyde, while the hydrogenation catalyst impregnation solution is a combination of specific metal oxides and organic matter.

[0003] The catalyst impregnation process involves the mass transfer process between the carrier and the impregnation liquid, that is, the liquid-solid mass transfer process. The efficiency and uniformity of the mass transfer will directly determine the density and dispersion of the active components, thereby affecting the catalytic performance of the catalyst. Therefore, for the catalyst impregnation process, using process intensification methods to improve the dispersion uniformity of its active components is an important means to optimize the catalyst preparation process.

[0004] At present, ultra-gravity reactors mainly come in two forms: wire mesh packing and stator-rotor. Since they can shear the fluid into nano-scale droplets or liquid lines through high-speed rotating cutting components, thereby enhancing the mixing and mass transfer efficiency and achieving the purpose of increasing the reaction rate, they are widely used in liquid-liquid reactions or gas-liquid reactions.

[0005] As for liquid-solid reactions, since the reaction solids are basically fine particles or powders, they are difficult to fix in wire mesh packing or stator and rotor structures. Therefore, there is no precedent in the public literature for using ultra-gravity multi-layer packing devices for liquid-solid reactions. Summary of the invention

[0006] The first technical problem to be solved by the present invention is to provide a system device for supergravity enhanced liquid-solid mass transfer. The system device can solve the technical problems of low efficiency and poor dispersion between small particles or powder and liquid mass transfer; the device can fix solid powder and enhance liquid dispersion.

[0007] The second technical problem to be solved by the present invention is to provide a method for enhancing liquid-solid mass transfer using the above system device.

[0008] To solve the above-mentioned first technical problem, the technical solution adopted by the present invention is as follows: :

[0009] A system device for enhancing liquid-solid mass transfer under ultra-gravity, comprising an external circulation ultra-gravity reactor, a circulation tank, a circulation pump, a motor, and a valve;

[0010] The external circulation high gravity reactor comprises a feed inlet, a discharge inlet, an air inlet, an air outlet, a liquid distributor and reactor internal components;

[0011] The reactor internals consist of columns, a packing area and a loading area;

[0012] The motor is detachably fixedly connected to the internal components of the reactor via a transmission shaft, and the rotation of the motor drives the internal components of the reactor to rotate;

[0013] The packing area and the loading area are provided with multiple layers, the multiple layers of packing area and the multiple layers of loading area are arranged concentrically and spaced apart, the upright column is fixed in the packing area or at the edge of the packing area; the packing area is used to fix the wire mesh packing and play the role of shearing the fluid; the loading area is used to load the solid powder, and the fluid sheared into nano-micro scale contacts with the solid powder, thereby strengthening the liquid-solid mixed mass transfer process;

[0014] The liquid distributor is arranged at the central cavity position of the reactor internal component;

[0015] The discharge port, the circulation tank, the circulation pump, the feed port, and the internal components of the reactor are sequentially connected through pipelines.

[0016] To solve the above second technical problem, the technical solution adopted by the present invention is as follows :

[0017] A method for enhancing liquid-solid mass transfer under ultra-gravity, comprising the following steps:

[0018] 1) Fixing the wire mesh filler in the filling area of ​​the reactor internals, loading the solid powder into the loading area of ​​the reactor internals, and sealing the reactor internals to prevent the powder from being thrown out;

[0019] 2) The impregnation liquid in the circulation tank is sent to the feed port of the supergravity reactor through a circulation pump, and the impregnation liquid is sprayed into the reactor internal components set in step 1) after passing through a liquid distributor;

[0020] 3) The first layer in the middle of the reactor internal component is a packing layer, and the impregnated liquid is cut into nano-scale liquid lines or droplets after passing through the rotating first layer of packing;

[0021] 4) The liquid line or liquid drop formed in step 3) passes through the first layer of filler in the reactor internals and enters the first filling area, and is absorbed by the solid powder filled there;

[0022] 5) The impregnation liquid that is not absorbed continues to be sheared on the second layer of filler, and the liquid lines and droplets formed thereafter are absorbed by the second layer of solid powder until the excess impregnation liquid passes through the outermost filler area and is thrown out of the reactor internal components; and finally flows back to the circulation tank through the discharge port;

[0023] 6) The impregnation liquid flowing back into the circulation tank repeats steps 2) to 5) until the powder reaches a saturated state of adsorbing the impregnation liquid;

[0024] 7) Remove the internal components of the reactor, pour out the solid powder, and obtain solid powder loaded with active components after washing, acid washing, drying and other steps.

[0025] Preferably, in step 1), each packing area of ​​the reactor internals is provided with a column, and the column is used to fix the wire mesh packing.

[0026] Preferably, in step 1), the mesh filler is 1-800 mesh, preferably 10-500 mesh, and the pore size of the selected mesh filler is smaller than the particle size of the solid powder to achieve the purpose of fixing the powder.

[0027] Preferably, in step 1), end covers are provided on the upper and lower end surfaces of the loading area.

[0028] Preferably, in step 1), the solid powder is one or more of activated carbon, graphene, metal oxide, molecular sieve, MOF material, COF material, diatomaceous earth, kaolin, silica gel, hollow glass microspheres, porous ceramics, carbon nanotubes, graphyne, and silicon carbide.

[0029] Preferably, in step 2), the liquid distributor adopts a circumferentially distributed opening design structure with a pore size of 0.5-5 mm, preferably 1-3 mm, to increase the initial velocity and dispersibility of the impregnation liquid.

[0030] Preferably, in step 3), the rotation speed of the internal components of the reactor is 300-3000 r / min, preferably 2000-2850 r / min.

[0031] Preferably, in step 5), the filler area has 3-20 layers, and the loading area has 3-20 layers.

[0032] Preferably, in step 6), the cycle time is 0.5-10 h, preferably 2-6 h;

[0033] Preferably, N2, O2, Ar, and CO2 gases are introduced into the ultragravity reactor through a gas inlet to provide the atmosphere required for the experiment.

[0034] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0035] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The present invention optimizes the design of the reactor internal components and divides the internal components into a packing area and a loading area. The packing area is used to fix the wire mesh packing, and the loading area is used to load the solid powder. The wire mesh packing in the packing area can shear the impregnation liquid into nano-microscale liquid lines and droplets, while the solid powder in the adjacent loading area directly contacts the liquid lines and droplets for mass transfer, thereby greatly enhancing the liquid-solid mass transfer efficiency. The traditional impregnation method basically puts the solid powder into the impregnation liquid and achieves the impregnation effect by stirring. This method has low mass transfer efficiency and poor dispersibility. It is difficult for the liquid to enter the powder. Therefore, the pore area cannot be fully utilized, and the prepared catalyst performance is poor. By using the supergravity impregnation method, the liquid-solid mass transfer efficiency can be greatly improved, the permeability of the solid can be improved, and the uniformity of the liquid dispersion in the solid can be increased, thereby improving the catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0039] Figure 1 The experimental flow chart of the ultra-gravity enhanced liquid-solid mass transfer of the present invention is shown;

[0040] Figure 2 A schematic diagram showing the structure of the internal components of the reactor of the present invention;

[0041] Figure 3 The EDS image of the sample prepared in Example 1 of the present invention is shown;

[0042] Figure 4 The EDS graph of the sample prepared in Comparative Example 1 of the present invention is shown;

[0043] Figure 5 ICP analysis of Ni content in samples prepared in Example 1 of the present invention and Comparative Example 1 is shown;

[0044] Figure 6 ICP analysis of Ce content in samples prepared in Example 2 of the present invention and Comparative Example 2 is shown;

[0045] Figure 7 ICP analysis of Fe content in samples prepared in Example 3 of the present invention and Comparative Example 3 is shown;

[0046] Figure 8 Atomic force microscope images of the surfaces of the acid-etched zirconium oxide slices prepared in Example 4 of the present invention and Comparative Example 4 are shown. DETAILED DESCRIPTION

[0047] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0048] As one aspect of the present invention, a system device for supergravity enhanced liquid-solid mass transfer includes an external circulation supergravity reactor, a circulation tank 1-1, a circulation pump 1-2, a motor 1-7, and a valve;

[0049] The external circulation high gravity reactor comprises a feed port 1-3, a discharge port 1-4, an air inlet 1-9, an air outlet 1-10, a liquid distributor 1-8 and reactor internal components;

[0050] The reactor internals consist of a column 1-11, a filler area 1-5 and a loading area 1-6;

[0051] The motor 1-7 is detachably fixedly connected to the internal components of the reactor through a transmission shaft, and the rotation of the motor drives the internal components of the reactor to rotate; those skilled in the art will understand that after the reaction is completed, the internal components of the reactor can be disassembled and removed from the supergravity reactor to replace the solid powder in the filling area;

[0052] The packing area 1-5 and the loading area 1-6 are provided with multiple layers, the multiple layers of packing area and the multiple layers of loading area are arranged concentrically and spaced apart, and the pillars 1-11 are fixed in the packing area or at the edge of the packing area; the packing area 1-5 is used to fix the wire mesh packing and play the role of shearing the fluid; the loading area 1-6 is used to load the solid powder, and the fluid sheared into nano-micro scale contacts with the solid powder, thereby strengthening the liquid-solid mixed mass transfer process; the particle size of the solid powder in the loading area 1-6 is larger than the aperture of the wire mesh packing, so as to prevent the solid powder from entering the wire mesh packing;

[0053] The liquid distributor 1-8 is arranged at the central cavity position of the reactor internal component;

[0054] The discharge port 1-4, the circulation tank 1-1, the circulation pump 1-2, the feed port 1-3, and the internal components of the reactor are connected in sequence through pipelines.

[0055] Based on the internal structure of the supergravity reactor and the existing deficiencies, the present invention optimizes the design of the internal components of the supergravity reactor and provides a supergravity reaction system device that can be used to enhance liquid-solid mass transfer.

[0056] As another aspect of the present invention, a method for enhancing liquid-solid mass transfer under high gravity comprises the following steps:

[0057] 1) Fixing the wire mesh filler in the filling area of ​​the reactor internals, loading the solid powder into the loading area of ​​the reactor internals, and sealing the reactor internals to prevent the powder from being thrown out;

[0058] 2) The impregnation liquid in the circulation tank is sent to the feed port of the supergravity reactor through a circulation pump, and the impregnation liquid is sprayed into the reactor internal components set in step 1) after passing through a liquid distributor;

[0059] 3) The first layer in the middle of the reactor internal component is a packing layer, and the impregnated liquid is cut into nano-scale liquid lines or droplets after passing through the rotating first layer of packing;

[0060] 4) The liquid line or liquid drop formed in step 3) passes through the first layer of filler in the reactor internals and enters the first filling area, and is absorbed by the solid powder filled there;

[0061] 5) The impregnation liquid that is not absorbed continues to be sheared on the second layer of filler, and the liquid lines and droplets formed thereafter are absorbed by the second layer of solid powder until the excess impregnation liquid passes through the outermost filler area and is thrown out of the reactor internal components; and finally flows back to the circulation tank through the discharge port;

[0062] 6) The impregnation liquid flowing back into the circulation tank repeats steps 2) to 5) until the powder reaches a saturated state of adsorbing the impregnation liquid;

[0063] 7) Remove the internal components of the reactor, pour out the solid powder, and obtain solid powder loaded with active components after washing, acid washing, drying and other steps.

[0064] According to some embodiments of the present invention, in step 1), each packing area of ​​the reactor internals is provided with a column, and the column is used to fix the wire mesh packing.

[0065] According to certain embodiments of the present invention, in step 1), in order to enhance mass transfer and prevent solid powder from being thrown out of the filling area during rotation, the pore size of the selected wire mesh filler needs to be smaller than the particle size of the powder; the wire mesh filler is 1-800 mesh, preferably 10-500 mesh.

[0066] According to some embodiments of the present invention, in step 1), in order to prevent the solid powder from being thrown out of the filling area during rotation, end covers are provided on the upper and lower end surfaces of the filling area, so as to seal the powder in the internal component with the end covers.

[0067] According to certain embodiments of the present invention, in step 1), the solid powder is one or more of activated carbon, graphene, metal oxides, molecular sieves, MOF materials, COF materials, diatomaceous earth, kaolin, silica gel, hollow glass microspheres, porous ceramics, carbon nanotubes, graphyne, and silicon carbide.

[0068] According to certain embodiments of the present invention, in step 2), the liquid distributor adopts a circumferentially distributed opening design structure with a pore size of 0.5-5 mm, preferably 1-3 mm, to increase the initial velocity and dispersibility of the impregnation liquid.

[0069] According to certain embodiments of the present invention, in step 3), the rotation speed of the internal components of the reactor is 300-3000 r / min, preferably 2000-2850 r / min.

[0070] According to certain embodiments of the present invention, in step 5), the size of the internal components can be designed according to the size of the reactor, and the number of packing areas and loading areas can be increased as much as possible to optimize the liquid-solid mass transfer effect; preferably, the packing area is 3-20 layers, and the loading area is 3-20 layers.

[0071] According to certain embodiments of the present invention, in step 6), the cycle time is 0.5-10 h, preferably 2-6 h;

[0072] According to certain embodiments of the present invention, gases such as N2, O2, Ar, CO2, etc. are introduced into the interior of the ultragravity reactor through a gas inlet to provide the atmosphere required for the experiment.

[0073] Example 1

[0074] A method for supergravity enhanced activated carbon adsorption of NiCl2 solution, comprising the following steps:

[0075] Fixing a wire mesh filler having a size of 80 meshes on the column of the reactor internal component;

[0076] 100 g of solid activated carbon was loaded into the loading area of ​​the reactor internals;

[0077] Prepare 500 mL of 5% NiCl2 solution and pour it into the circulation tank, and connect the circulation tank, circulation pump and high gravity reactor;

[0078] Turn on the ultragravity reactor and set the speed to 2000 rpm;

[0079] Turn on the circulation pump and set the feed flow rate to 20L / h;

[0080] The temperature was controlled at 30°C and the feed was circulated for 2 h;

[0081] After the cycle is completed, the internal components of the reactor are removed, the solid activated carbon is poured out, and it is pickled with hydrochloric acid at 50°C for 2 hours, and then washed with deionized water for 3 times until the pH of the solution is neutral, and the product is dried at 90°C for 48 hours.

[0082] Figure 3 This is the EDS graph of the solid activated carbon sample adsorbed with Ni ions prepared in Example 1 of the present invention.

[0083] Example 2

[0084] A method for supergravity enhanced molecular sieve adsorption of CeCl3 solution comprises the following steps:

[0085] Fixing a wire mesh filler with a size of 300 meshes on the column of the reactor internals;

[0086] 50 g of molecular sieve powder was loaded into the loading area of ​​the reactor internals;

[0087] Prepare 500 mL of 5% CeCl2 solution and pour it into the circulation tank, and connect the circulation tank, circulation pump and high gravity reactor;

[0088] Turn on the ultragravity reactor and set the speed to 2500 rpm;

[0089] Turn on the circulation pump and set the feed flow rate to 40L / h;

[0090] The temperature was controlled at 30°C and the feed was circulated for 3 hours;

[0091] After the cycle is completed, the internal components of the reactor are removed, the molecular sieve powder is poured out, and it is pickled with hydrochloric acid at 50°C for 3 hours, and then washed with deionized water for 3 times until the pH of the solution is neutral, and the product is dried at 80°C for 48 hours.

[0092] Figure 6 This is an ICP analysis chart of the Ce content in the molecular sieve powder samples adsorbing Ce ions prepared in Example 2 and Comparative Example 2.

[0093] Example 3

[0094] A method for supergravity-enhanced MOF material adsorption of Fe(NO3)3 solution, comprising the following steps:

[0095] Fixing a wire mesh filler with a size of 800 meshes on the column of the reactor internals;

[0096] 10 g of MOF powder was loaded into the loading area of ​​the reactor internals;

[0097] Prepare 100 mL of 2 mg / mL Fe(NO3)3 solution and pour it into the circulation tank, and connect the circulation tank, circulation pump and high gravity reactor;

[0098] Turn on the ultra-gravity reactor and set the speed to 2800 rpm;

[0099] Turn on the circulation pump and set the feed flow rate to 10L / h;

[0100] The temperature was controlled at 50°C and the feed was circulated for 2 h;

[0101] After the cycle, the internal components of the reactor were removed, the MOF powder was poured out, and pickled with sulfuric acid at 50°C for 3 h, then washed with deionized water and methanol three times until the pH of the solution was neutral, and the product was dried at 80°C for 12 h.

[0102] Figure 7 This is an ICP analysis chart of the Fe content in the MOF powder samples adsorbing Fe ions prepared in Example 3 and Comparative Example 3.

[0103] Example 4

[0104] A method for ultra-gravity strengthening of zirconia acid etching of dental materials, comprising the following steps:

[0105] Fixing a wire mesh filler with a size of 100 meshes on the column of the reactor internals;

[0106] 50 g of zirconium oxide flakes were fixed to the loading area of ​​the reactor internals;

[0107] Prepare 300 mL of 0.5 mol / L hydrochloric acid solution and pour it into the circulation tank, and connect the circulation tank, circulation pump and high gravity reactor;

[0108] Turn on the ultra-gravity reactor and set the speed to 1800 rpm;

[0109] Turn on the circulation pump, set the feed flow rate to 50 L / h, and circulate the reaction at room temperature for 3 h;

[0110] After the cycle was completed, the internal components of the reactor were removed, the zirconium oxide flakes were poured out, and they were washed three times with deionized water until the washing liquid was neutral. The zirconium oxide flakes were dried at 100°C for 12 h for subsequent characterization.

[0111] Figure 8 Atomic force microscope images of the surfaces of the acid-etched zirconium oxide slices prepared in Example 4 and Comparative Example 4 are shown.

[0112] Comparative Example 1

[0113] Example 1 was repeated, except that the same mass of solid activated carbon was placed in a stirred reactor, the same volume and concentration of NiCl2 solution was added to the stirred reactor, the stirring paddle speed was set to 1000 rpm, the temperature was controlled to 30°C, and the stirring time was 2 h; after the stirring was completed, the solid activated carbon was taken out, pickled with hydrochloric acid at 50°C for 2 h, and then washed with deionized water for 3 times until the pH of the solution was neutral, and the product was dried at 90°C for 48 h.

[0114] Figure 4 This is the EDS image of the solid activated carbon sample adsorbing Ni ions prepared in Comparative Example 1. Figure 5 ICP analysis of Ni content in the samples prepared in Example 1 of the present invention and Comparative Example 1.

[0115] It can be seen from this that the use of ultra-gravity technology can increase the impregnation amount and uniformity of Ni ions in activated carbon and enhance the liquid-solid mass transfer efficiency.

[0116] Comparative Example 2

[0117] Example 2 was repeated, except that the same mass of molecular sieve powder was placed in a stirred reactor, the same volume and concentration of CeCl2 solution was added to the stirred reactor, the stirring paddle speed was set to 1000 rpm, the temperature was controlled to 30°C, and the stirring time was 3 h; after the stirring was completed, the molecular sieve powder was taken out, pickled with hydrochloric acid at 50°C for 3 h, and then washed with deionized water for 3 times until the pH of the solution was neutral, and the product was dried at 80°C for 48 h.

[0118] Figure 6 This is an ICP analysis chart of the Ce content in the molecular sieve powder samples adsorbing Ce ions prepared in Comparative Example 2 and Example 2.

[0119] It can be seen from this that the use of ultra-gravity technology can increase the impregnation amount of Ce ions in the molecular sieve powder and enhance the liquid-solid mass transfer efficiency.

[0120] Comparative Example 3

[0121] Example 3 was repeated, except that the same mass of MOF powder was placed in a stirred reactor, the same volume and concentration of Fe(NO3)3 solution was added to the stirred reactor, the stirring blade speed was set to 1000 rpm, the temperature was controlled to 50°C, and the stirring time was 2 hours. After the stirring was completed, the MOF powder was taken out, pickled with sulfuric acid at 50°C for 3 hours, and then washed with deionized water and methanol 3 times until the pH of the solution was neutral, and the product was dried at 80°C for 12 hours.

[0122] Figure 7This is an ICP analysis chart of the Fe content in the MOF powder samples adsorbing Fe ions prepared in Comparative Example 3 and Example 3.

[0123] It can be seen from this that the use of ultra-gravity technology can increase the adsorption of Fe ions in MOF materials and enhance the liquid-solid mass transfer efficiency.

[0124] Comparative Example 4

[0125] Example 4 was repeated, except that: the same mass of zirconia flakes were placed in a stirred reactor, a hydrochloric acid solution of the same volume and concentration was added to the stirred reactor, the stirring paddle speed was set to 1000 rpm, and stirring was carried out at room temperature for 3 hours; after the stirring was completed, the zirconia flakes were taken out, washed three times with deionized water until the washing liquid was neutral, and the zirconia flakes were dried at 100°C for 12 hours for subsequent characterization.

[0126] Figure 8 This is an atomic force microscope image of the surface of the zirconium oxide slice after acid etching prepared in Comparative Example 4 and Example 4.

[0127] It can be seen from this that the use of ultra-gravity technology can increase the acid etching degree and roughness of zirconia materials and enhance the liquid-solid mass transfer efficiency.

[0128] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A system device for enhancing liquid-solid mass transfer under ultra-gravity, characterized in that: Including external circulation ultra-gravity reactor, circulation tank, circulation pump, motor and valve; The external circulation high gravity reactor comprises a feed inlet, a discharge inlet, an air inlet, an air outlet, a liquid distributor and reactor internal components; The reactor internals consist of columns, a packing area and a loading area; The motor is detachably fixedly connected to the internal components of the reactor via a transmission shaft, and the rotation of the motor drives the internal components of the reactor to rotate; The packing area and the loading area are provided with multiple layers, the multiple layers of packing area and the multiple layers of loading area are arranged concentrically and spaced apart, and the upright column is fixed in the packing area or at the edge of the packing area; The liquid distributor is arranged at the central cavity position of the reactor internal component; The discharge port, the circulation tank, the circulation pump, the feed port, and the internal components of the reactor are sequentially connected through pipelines.

2. A method for high gravity enhanced liquid-solid mass transfer using the system device as claimed in claim 1, characterized in that: The following steps are involved: 1) Fixing the wire mesh filler in the filling area of ​​the reactor internals, loading the solid powder into the loading area of ​​the reactor internals, and sealing the reactor internals to prevent the powder from being thrown out; 2) The impregnation liquid in the circulation tank is sent to the feed port of the supergravity reactor through a circulation pump, and the impregnation liquid is sprayed into the reactor internal components set in step 1) after passing through a liquid distributor; 3) The first layer in the middle of the reactor internal component is a packing layer, and the impregnated liquid is cut into nano-scale liquid lines or droplets after passing through the rotating first layer of packing; 4) The liquid line or liquid drop formed in step 3) passes through the first layer of filler in the reactor internals and enters the first filling area, and is absorbed by the solid powder filled there; 5) The impregnation liquid that is not absorbed continues to be sheared on the second layer of filler, and the liquid lines and droplets formed thereafter are absorbed by the second layer of solid powder until the excess impregnation liquid passes through the outermost filler area and is thrown out of the reactor internal components; and finally flows back to the circulation tank through the discharge port; 6) The impregnation liquid flowing back into the circulation tank repeats steps 2) to 5) until the powder reaches a saturated state of adsorbing the impregnation liquid; 7) Remove the internal components of the reactor, pour out the solid powder, and obtain solid powder loaded with active components after washing, acid washing, drying and other steps.

3. The method for enhancing liquid-solid mass transfer under high gravity according to claim 2, characterized in that: In step 1), each packing area of ​​the reactor internals is provided with a column, which is used to fix the wire mesh packing.

4. The method for enhancing liquid-solid mass transfer under high gravity according to claim 2, characterized in that: In step 1), the mesh filler is 1-800 mesh, preferably 10-500 mesh.

5. The method for enhancing liquid-solid mass transfer under high gravity according to claim 2, characterized in that: In step 1), end covers are provided on the upper and lower end surfaces of the loading area.

6. The method for enhancing liquid-solid mass transfer under high gravity according to claim 2, characterized in that: In step 1), the solid powder is one or more of activated carbon, graphene, metal oxide, molecular sieve, MOF material, COF material, diatomaceous earth, kaolin, silica gel, hollow glass microspheres, porous ceramics, carbon nanotubes, graphyne, and silicon carbide.

7. The method for enhancing liquid-solid mass transfer under high gravity according to claim 2, characterized in that: In step 2), the liquid distributor adopts a circumferentially distributed opening design structure with a pore size of 0.5-5 mm, preferably 1-3 mm, to increase the initial velocity and dispersibility of the impregnation liquid.

8. The method for enhancing liquid-solid mass transfer under high gravity according to claim 2, characterized in that: In step 3), the rotation speed of the internal components of the reactor is 300-3000 r / min, preferably 2000-2850 r / min.

9. The method for enhancing liquid-solid mass transfer under high gravity according to claim 2, characterized in that: In step 5), the filler area has 3-20 layers, and the loading area has 3-20 layers.

10. The method for enhancing liquid-solid mass transfer under high gravity according to claim 2, characterized in that: In step 6), the cycle time is 0.5-10h, preferably 2-6h; Preferably, N2, O2, Ar, and CO2 gases are introduced into the ultragravity reactor through a gas inlet to provide the atmosphere required for the experiment.

Citation Information

Patent Citations

  • Multi-stage material feeding supergravity liquid-liquid reactor apparatus and applications thereof

    CN105080446A

  • Fluidized solids technique

    US3169835A

Cited By

  • Integrated ultrasonic-assisted submerged rotating packed bed liquid-solid dispersion device and application

    CN122828669A